Enhancing EFL learning in college through performance festivals – a holistic approach - Shiozawa, Yasuko; Moody, Miho (SCENARIO: Journal for Performative Teaching, Learning, Research, 2016)
A group of university teachers have worked to organize and host an annual performance festival for 20 years. About a hundred students from several universities gather and perform a variety of oral activities every year. Students engage with everything from everyday events to long-standing global issues through drama, and thus this festival is a unique educational experience. Touching on the current status of EFL (English as Foreign Language) within Japanese Universities, this paper aims to discuss the significance of the festival through briefly describing some sample performances and their process of preparation. While the festival is not in any way competitive, both students and teachers attending are expected to provide some form of feedback to every performance viewed. Expressing themselves at the festival is especially meaningful in the context of EFL, where no immediate need to use the language in their daily life exists for the typical Japanese student. Additionally, participants are likely to gain a sense of achievement and confidence through the process and encouraging response at the festival. Finally, students learn to collaborate efficiently and build leadership skills. Challenges in terms of preparation and management of the festival are also discussed in this paper.